Peritoneal Cryptococcosis in a Dog - De Oliveira Carvalho da Silva, Beline Mergulhão (2021)
Background: Cryptococcosis is an opportunistic, systemic mycotic disease caused by yeasts of genus Cryptococcus. Cryptococcus neoformans might cause serious public health problems, as they can be transmitted to humans, domestic and wild animals. In cats and dogs, the main site of infection is the upper lower respiratory tract, however, the infection can extend and affect other sites in the organism, however, the peritoneal manifestation of the disease is rare. Thus, the present work aims to report a case of cryptococcosis in a canine, mixed breed, female, adult, from the Metropolitan Region of Belém, PA, Brazil. Case: A mixed breed dog, female, adult was admitted in a veterinary hospital at Belém, presenting abdominal discomfort and, after the clinical examination, emergency exploratory laparotomy was indicated, and it were observed disseminated lesions in the abdominal cavity, with multiple nodules attached to the peritoneum and intestinal serosa and bladder, uterus, among other organs. Fragments from the surgical biopsy were fixed, and processed routinely according to the techniques for histological tissue processing. Histological examination revealed a predominance of granulomatous lesions in peritoneum and mesentery organs. It was observed a discrete inflammatory reaction of macrophages, epithelioid cells and giant cells, many in phagocytosis of spherical or ovoid organisms, with a thick capsule and a clear perinuclear halo. In the PAS staining, the Cryptococcus conidia presented eosinophilic characteristics and some of them had the capsule well demarcated, which was shown to be radiated. Also it was possible to see the budding yeast and in the Grocott stain, the Cryptococcus stained in black. Discussion: Cryptococcosis with peritoneal involvement in animals is rarely reported in the literature. Cryptococcus is a fungus that presents tropism by the central nervous system and nasal cavity, however atypical presentations have been reported, especially at the level of the abdominal cavity (intestines and mesentery). It is believed that the gastrointestinal tract is the gateway for ascending contamination, or that the contamination can occur by fungal ingestion. The lesions presented a multiple distribution, with isolated and coalescent nodules adhered to the peritoneum and adjacent structures. The literature reports two cases of dogs with intra-abdominal cryptococcosis, in which, macroscopically, granulomatous formations were observed in the jejunum, with lymph nodes and mesentery. Microscopically, a discrete inflammatory infiltrate of macrophages and lymphocytes were observed. Some areas with granulomatous reaction, lymphocytes, epithelioid macrophages and giant cells and, in other areas, yeasts in the cytoplasm were observed. The yeasts were spherical or ovoid, surrounded by a thick capsule of polysaccharide. The periodic acid Schiff (PAS) and silver impregnation (Grocott) staining were used to highlight structures of the Cryptococcus wall which were presented by a strong stained polysaccharide capsule. It must be emphasized the zoonotic potential of cryptococcosis, a disease that can affect both animals and humans. Cryptococcosis in humans normally occurs when the fungus accesses the airways through inhalation and ranges from asymptomatic pulmonary colonization to compromised meninges, causing the human patient’s life-threatening condition. In the present report, the diagnosis of cryptococcosis was established through histopathological and histochemical examination of the fungal structure, which were determinant in the etiological diagnosis of cryptococcosis.